Tinjuan Pustaka: Hubungan Jenis Kelamin dan Hormon Androgen dengan Kejadian Dry-Eye Disease - Fairuz Hanan, Sifa’Syaharani; Rengganis Wardani, Dyah Wulan Sumekar; Rudiyanto, Waluyo; Himayani, Rani (Medula, 2024)
Dry eye disease (DED) is a multifactorial condition on the surface of the eye that occurs due to disruption of tear film homeostasis with manifestations of symptoms such as tear film instability, hyperosmolarity, inflammation, eye surface damage, and neurosensory abnormalities. DED can occur due to decreased eye fluid production or increased tear evaporation which is generally caused by meibomian gland dysfunction. The global prevalence of DED ranges from 5-50%, with women having a higher risk than men. The prevalence of dry eye in women (3.2 million) is higher than in men (1.6 million) aged over 50 years. Asian ethnicity is the most consistent risk factor for DED. The female gender factor is a risk in the development of DED with increasing age. The pathophysiological mechanisms of DED can be influenced by differences in endocrine function related to sex, especially androgen, estrogen and other hormones. The meibomian and lacrimal glands are target organs for androgen hormones, and low androgen activity can cause meibomian gland dysfunction and inflammation of the lacrimal glands, contributing to the occurrence of DED. In addition, differences in gene expression affect mucin production by the cornea and conjunctiva, as well as other hormonal involvement can also affect eye health and cause dry eye symptoms. Further understanding of the relationship between gender, hormones, and pathophysiological mechanisms of DED may aid the development of more effective treatment strategies.